The Influence of Project Based Learning Strategy on Learning Outcomes in Computer Science Subjects at Vocational High School - Wijaya, Sadam Subandi Karta; Prihatin, Relly; Palupi, Rismaka (Indonesian Journal of Learning and Instructional Innovation, 2026)
Technological developments in the Industrial Revolution 4.0 era require the world of education to implement learning strategies that can improve critical thinking skills and student creativity, especially in Informatics subjects in Vocational High Schools (SMK), but the dominance of conventional strategies causes student learning outcomes to be less than optimal. This study aims to examine the improvement, differences, and the effect of implementing Project Based Learning (PjBL) strategies on Informatics learning outcomes of class X Health Services students at SMK Negeri 1 Banyudono. This study used a quantitative approach with a quasi-experimental design, involving class X LK 1 as the experimental class receiving the PjBL strategy and class X LK 2 as the control class using conventional learning. Data collection used a pre-test and post-test, then analyzed using paired sample t-tests, independent sample t-tests, and the N-Gain test. The results indicated a significant increase in learning outcomes in the experimental class with a calculated t-value of 23.610, and a significant difference between the experimental and control classes with a calculated t-value of 10.915. The average N-Gain value of 0.55 is in the moderate category. Based on these findings, it is concluded that the Project Based Learning strategy has been proven to have a significant influence on student learning outcomes through collaborative activities and project completion, thus potentially being an effective alternative learning strategy in informatics subjects.